Pemberdayaan Ekonomi Pesantren Salafiyah Al-Barokah Melalui Pelatihan Inovasi Pembuatan Bakso Jamur - Ima Maisaroh; Nina Yuliana; Muhammad Jaiz (LP3MKIL, 2022)
Abstract This Community Service Program is the Economic Empowerment of Salafiyah Islamic Boarding Schools. Implemented through the Innovation Training for the Making of Mushroom Meatballs at the Pesantren Al-Barokah in Serang Regency. This activity is intended to help strengthen the institutional and economic capacity so that it can further improve the quality of its education services. Pesantren Al-Barokah is an independent, out-of-school educational institution that provides “optimal” educational services. The students are facilitated 1) religious education typical of the pesantren, 2) Pursuing Package education so that later they have formal legality (Equality Certificate), 3) skills in mushroom cultivation, 4) adequate accommodation and learning facilities. Problem: Because the tuitions is very light, pesantren income is relatively limited so that the operational costs of the pesantren are very dependent on the organizers. This pesantren has an oyster mushroom cultivation business unit, but because there is no creative economic process, it has not produced optimal income. Solutions to these problems were given entrepreneurship counseling and training on making mushroom meatballs as an effort to increase the value added of managed mushroom cultivation.